The use of veno-arterial extra corporeal membrane oxygenation for hemodynamics support during high-risk percutaneous coronary intervention - Wael Samy; Helmy Elghawaby; Akram Abdelbary; Hany Zakaria Mohamed; Alia Hassan Abdel Fattah (Egyptian Journal of Critical Care Medicine)
Abstract Background Complex coronary artery disease still a major health problem, whether high-risk PCI on V-A ECMO or not is a better choice. Aim and objectives The study is designed to assess the outcomes of using V-A ECMO on high-risk PCI procedures. Patients and methods A prospective interventional study performed on patients with viable ischemic myocardium who refused CABG, syntax score>22, excluding scarred myocardium. V-A ECMO (Fem-Fem configuration) will be initiated during elective high-risk PCI procedure, compared to patients who underwent high-risk PCI refusing ECMO, also excluding patients suffering from acute decompensated heart failure. Results This is a case-control study where total of 20 patients were identified, 10 patients underwent high-risk PCI on V-A ECMO support, (Control group) 10 patients underwent high-risk PCI without V-A ECMO; our study showed a statistically significant higher SYNTAX score in group 1 than that in group 2, p value 0.025, no statistically significance difference between the number of cases with left main lesions, unprotected LM and MVD between group 1 and group 2, average ECMO duration of 2.5 h, 6 patients on awake ECMO, and statistically non-significant difference between NYHA class between group 1 and group 2. Also our study showed no statistically difference between LV EF before and after PCI in both groups; in group 1, eight patients had complete revascularization in one session while in group 2 only seven patients had complete revascularization; one patient in group 1 had VT while in group 2, one patient had VF and another one suffered of asystole; group 1 patients all discharged home within 1 week while group 2 had two mortalities during PCI. Conclusion ECMO can be successfully used to facilitate elective high-risk PCI minimizing risk of cardiovascular complications.